Long-term dynamics of multiple sclerosis iron rim lesions - Weber, Claudia Ellen; Wittayer, Matthias Sebastian; Kraemer, Matthias; Dabringhaus, Andreas; Bail, Kathrin; Platten, Michael; Schirmer, Lucas; Gass, Achim; Eisele, Philipp (Multiple Sclerosis and Related Disorders, 2022)
BACKGROUND: Several studies have pointed out that seemingly chronic multiple sclerosis (MS) lesions may also be in inflammatory states. In pathological studies, up to 40% of chronic MS lesions are characterized as "chronic active" or "smoldering" lesions that are characterized by a rim of iron-laden proinflammatory macrophages/microglial cells at the lesion edge with low-grade continuous myelin breakdown. In vivo, these lesions can be visualized as "iron rim lesions" (IRLs) on susceptibility-weighted imaging (SWI). The aim of this study was to investigate the long-term dynamics of IRLs in vivo for a more detailed evolution of dynamic lesion volume changes occurring over time. - METHODS: We retrospectively identified patients with MS who were followed for at least 36 months (up to 72 months) and underwent at least an annual MRI on the same 3 Tsystem. Using Voxel-Guided Morphometry (VGM) we investigated regional volume changes within lesions and correlated these findings with SWI for the presence of a characteristic hypointense lesion rim. To estimate tissue damage, apparent diffusion coefficient (ADC) values for every lesion at baseline and follow-up MRIs were determined. - RESULTS: Forty-three patients were included in the study. Overall, we identified 302 supratentorial non-confluent MS lesions (52 persistent IRLs, nine transient IRLs, 228 non-IRLs and 13 acute contrast-enhancing lesions). During follow-up, persistent IRLs significantly enlarged, whereas non-IRLs showed a tendency to shrink. At baseline MRI, ADC values were significantly higher in persistent IRLs (1.23 × 10-3 mm/s2) compared to non-IRLs (1.01 × 10-3 mm/s2; p < 0.001), but not compared to transient IRLs (1.06 × 10-3 mm/s2; p = 0.15) and contrast-enhancing lesions (1.15 × 10-3 mm/s2; p = 1.0). During follow-up, ADC values significantly increased more often in persistent IRLs compared to all other lesion types (p < 0.0001). - CONCLUSIONS: Our long-term data demonstrate that persistent IRLs enlarge during disease duration, whereas non-IRLs show a tendency to shrink. Furthermore, IRLs are associated with sustained tissue damage, supporting the notion that IRLs could represent a new imaging biomarker in MS.
Available online 18 October 2021
Gesehen am 02.09.2022